IMPLEMENTATION OF THE PJBL (PROJECT-BASED LEARNING) MODEL TO IMPROVE STUDENT CREATIVITY - Muhammad Chusaini Alfin; Khofifatu Rohmah Adi; Elly Panca Kurniawati (Universitas Lambung Mangkurat, 2026)
This research discusses the creativity skills carried out by researchers because they want to improve and increase learning creativity by using the Project-Based Learning learning model, for this research was carried out at SMP Negeri 1 Bangsal. While the type of research conducted by the researcher is a type of collaborative class action research consisting of 2 learning cycles where each cycle is carried out 2 meetings, while for the structure and stages of this research in accordance with PTK in general, the first is planning, the second is the implementation (action), the third is observation), and the last is reflection and (Evaluation). For the subject of this study, all students of class VII/A totaling 31. Meanwhile, the instruments used by the researcher were in the form of learning observation sheets, questionnaires to determine the increase in creativity, as well as the results of learning assessments and documentation. The results and discussion of this research will be emphasized on the analysis of data processing from the results of the questionnaire, product assessment, and the percentage of completeness of the learning material. From this study, the researcher found an increase in creativity from the indicators that have been made and implemented.